2021
DOI: 10.3389/fonc.2021.676041
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Implications of CDK4/6 Inhibitors for the Treatment of NSCLC

Abstract: Cyclin-dependent kinases (CDKs) are key regulators of cell cycle progression in malignant tumor cells and play an important role through complex molecular interactions. Dysregulation of CDK dependent pathways is often found in non-small cell lung cancer, which indicates its vulnerability and can be used in clinical benefit. CDK4/6 inhibitors can prevent tumor cells from entering the G approved 1 and S phases, which have been studied in a series of explorations and brought great clinical effect to patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…Cell cycle dysregulation, implicated in malignant transformation and tumor progression, occurs in more than 90% of lung cancers, partially due to the aberrant activity of Cyclin-dependent kinases (CDK)–cyclin–RB pathways CDK4 and CDK6 can form complex with D-type cyclins, sequentially phosphorylate the Rb tumor suppressor protein, release E2F1, and thereby facilitate cell cycle progression Inhibiting CDK4/6 impairs cell cycle progression, suppresses tumor cell proliferation, and induces senescence. Several highly specific CDK4/6 inhibitors (Palbociclib, Ribociclib, and Abemaciclib), approved by the FDA for advanced metastatic breast cancer, showed great antitumor effects in preclinical lung cancer models [ 35 ] and have also been applied in clinical trials of lung cancer [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle dysregulation, implicated in malignant transformation and tumor progression, occurs in more than 90% of lung cancers, partially due to the aberrant activity of Cyclin-dependent kinases (CDK)–cyclin–RB pathways CDK4 and CDK6 can form complex with D-type cyclins, sequentially phosphorylate the Rb tumor suppressor protein, release E2F1, and thereby facilitate cell cycle progression Inhibiting CDK4/6 impairs cell cycle progression, suppresses tumor cell proliferation, and induces senescence. Several highly specific CDK4/6 inhibitors (Palbociclib, Ribociclib, and Abemaciclib), approved by the FDA for advanced metastatic breast cancer, showed great antitumor effects in preclinical lung cancer models [ 35 ] and have also been applied in clinical trials of lung cancer [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several antagonists with excellent activity against CDK4 and CDK6 have been approved for treatment of breast cancer, which restore cell cycle control at the G1/S transition and significantly extend patients' lives [12,[25][26][27][28]. Furthermore, the clinical benefits of these inhibitors for lung cancer patients are currently under evaluation, and promising results have been observed in certain subtypes of lung cancer patients [29][30][31]. In the current study, we found that decreased FAM117A expression in lung cancer cells warrants cell cycle progression by releasing the G1/S checkpoint, which could be fully rescued by CDK4/6 inhibitors and provides a molecular basis for treatment of lung cancer patients with CDK inhibitors or other cell cycle modulators.…”
Section: Discussionmentioning
confidence: 99%
“…Combinations with inhibitors of molecules involved in growth factor signaling including EGFR, mTOR, MEK and PI3Ka, have been shown to enhance anticancer effects. 54 Moreover, palbociclib has been shown to be an effective combination partner with gefitinib in preclinical studies of lung cancer, 55 and results from an in vitro study of palbociclib and osimertinib suggested the combination may overcome acquired resistance to osimertinib. 56 A combinatorial benefit was also observed in NSCLC cells treated with ribociclib and nazartinib (not FDA approved).…”
Section: Markers Of Sensitivitymentioning
confidence: 99%